SCALE Diabetes: Continually Dosed Liraglutide May Aid Weight Loss in T2DM - Lederman, Lynne (MD Conference Express, 2014)
This article presents the results of the Effect of Liraglutide on Body Weight in Overweight or Obese Subjects With Type 2 Diabetes trial [SCALE Diabetes; NCT01272232]. This large, multicenter, international trial investigated the efficacy and safety of 56 weeks of treatment with 2 doses of liraglutide, 3.0 and 1.8 mg, compared with placebo, as an adjunct to diet and exercise in inducing and maintaining weight loss in overweight or obese individuals with type 2 diabetes mellitus (T2DM).